Extra intravenous Ustekinumab reinduction is an effective optimization strategy for patients with refractory Crohn’s disease - Yao, Jiayin; Peng, Xiang; Zhong, Yingkui; Su, Tao; Bihi, Adam; Zhao, Junzhang; Liu, Tao; Wang, Wei; Hu, Pinjin; Zhang, Min; Zhi, Min (Frontiers in Medicine, 2023)
Objectives Ustekinumab (UST) optimization strategies, including shortening intervals and intravenous reinduction, should be administered to patients with partial or loss of respond. Evidence comparing these types of optimization treatments is limited. We evaluated the efficacy and safety of weight-based UST intravenous reinduction in patients with refractory Crohn’s disease (CD). Methods This was a single-center retrospective observational study. Optimization strategies were designed for patients showing partial or loss of response to standardized UST therapy. Clinical, biochemical, and endoscopic response and remission rate were determined by Crohn’s disease activity index (CDAI), C-reactive protein (CRP) levels, and SES-CD evaluation. UST trough concentrations were detected and adverse events were recorded. Results A total of 128 patients receiving UST optimization therapies were included, with 105 patients administered shortening intervals of q8w or q4w, and 23 receiving intravenous reinduction followed by subcutaneous q8w or q4w. The follow-up duration for the shortening interval and reinduction cohorts were 15.0 (10.0, 31.0) and 23.0 (13.0, 70.0) weeks, respectively. A significant CDAI delta variation pre-and post-treatment could be found between groups [17.0 (−4.4, 65.9) vs. 69.0(10.7, 151.0), p = 0.013]. the trough concentration of UST increased [2.5 (1.3, 5.3) vs. 1.1 (0.5, 2.3), p = 0.001] after intravenous reinduction. Clinical and endoscopic remission were achieved in 69.6 and 31.8% of patients in the intravenous reinduction cohort, and 62.9 and 22.2% of patients in the shortening interval cohort, respectively. No significant difference was found between groups regarding safety. Conclusion Intravenous reinduction brought about favorable recapture of clinical and endoscopic remission, and should have significant priority over the strategy of merely shortening drug intervals, which should be launched before switching to other biologics targeting different inflammatory pathways. Clinical Trial Registration: identifier NCT04923100. https://classic.clinicaltrials.gov/ct2/show/NCT04923100?id=04923100&draw=2&rank=1